行星轮系卷扬机传动机构的运动仿真分析 - 石加联; 于占忠; 姜奎波 (Jixie chuandong)
On the basis of the operation principle for the hoist of planetary gear train,analysis of transmission mechanism and calculation of the transmission ratio are carried out.Using the Pro/E software,solid modeling,assemble,checking interfering,movement simulation analysis of the mechanism are carried on.The operation course of the transmission for hoist of planetary gear train is simulated by cartoon.In the course of demonstrating playback,simulation follows the designated key,and its motion curve is obtained.Contrasting with result of calculation of the theory and the computer simulation,it is verified that the models of motion simulation are correct in Pro/E and the result is credible.